Kókai-Nagy, Viktor – Vér, Ádám (eds.), Josephus and the Maccabees, Berlin–Boston, Walter de Gruyter, 2025, pp. 238, ISBN 978-3-11-914918-1, ISSN 1865-1666 - DEBRECZENI, Ákos József (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2026)
We cannot form a complete picture of the biblical stories without knowledge of Josephus and the Maccabees. Although the books of the Maccabees have been omitted from the Protestant biblical canon, anyone who is curious about what happened between the Old Testament and the New Testament must read Josephus’s writings and study the stories of the Maccabees. The editors are Dr Viktor Kókai-Nagy, Assistant Professor of the DRTU Department of Biblical Theology and the History of Religion and USJ Department of Biblical Studies and Dr Ádám Vér, Assistant Professor at ELTE Institute of Ancient and Classical Studies. The collection of studies holds the presentations given at the Josephus and the Maccabees conference held in Komárno Slovakia in 2024, apart from Steve Mason’s introductory study written upon special request. The volume thus boasts ten studies, some of which are in German as well as English. The authors of the volume are well-known researchers, notably Steve Mason, who is an authority on Josephus. The focus of the conference was to look at Josephus and the Maccabees from a new perspective, an intention that is well reflected in the studies and titles included in the volume. The authors have done an excellent job of showing how Josephus, the Book of Maccabees, as well as historical developments mutually influence one another. The topics are unusual and, in some places, provocative. Thanks to the theme of the conference, the authors, and the editors, all studies included are easy to understand, logically structured, nicely delineated, and sometimes complementary. The result is a collection of studies in which the individual works are monolithic, making the topic easy to understand.